Application of Ruscheweyh q-differential operator to analytic functions of reciprocal order - MAHMOOD , Shahid; MUSTAFA, Saima; KHAN, Imran (Studia Universitatis Babeș-Bolyai Mathematica, 2020)
The core object of this paper is to define and study new class of analytic function using Ruscheweyh q-differential operator. We also investigate a number of useful properties such as inclusion relation, coefficient estimates, subordination result,for this newly subclass of analytic functions. Mathematics Subject Classification (2010): 30C45, 30C50.